Increased Myosin light chain 9 expression during Kawasaki disease vasculitis - Kobayashi, Hironobu; Kimura, Motoko Y.; Hasegawa, Ichita; Suganuma, Eisuke; Ikehara, Yuzuru; Azuma, Kazuhiko; Ito, Toshihiro; Ebata, Ryota; Kurashima, Yosuke; Kawasaki, Yohei; Shiko, Yuki; Saito, Naoki; et al. (Frontiers in Immunology, 2023)
Kawasaki disease (KD) is an acute systemic vasculitis that predominantly afflicts children. KD development is known to be associated with an aberrant immune response and abnormal platelet activation, however its etiology is still largely unknown. Myosin light chain 9 (Myl9) is known to regulate cellular contractility of both non-muscle and smooth muscle cells, and can be released from platelets. Here we found that plasma Myl9 levels were significantly higher in KD patients during the acute phase compared with healthy controls or patients with other febrile illnesses, declined following IVIG therapy in IVIG-responders but not in non-responders. In vitro, platelets from KD patients released Myl9 independently of thrombin stimulation. In the Lactobacillus casei cell wall extract (LCWE) mouse model of KD vasculitis, Myl9 was detected in cardiac tissue at an early stage before inflammatory cell infiltration was observed. In tissues obtained at autopsy from KD patients, the highest Myl9 expression was observed in thrombi during the acute phase and in the intima and adventitia of coronary arteries during the chronic phase. Thus, our studies show that Myl9 expression is significantly increased during KD vasculitis and that Myl9 levels may be a useful biomarker to estimate inflammation and IVIG responsiveness to KD.